2016
DOI: 10.2196/jmir.5531
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Physical Activity and Sedentary Behavior in a Free-Living Context: A Pragmatic Comparison of Consumer-Based Activity Trackers and ActiGraph Accelerometry

Abstract: BackgroundActivity trackers are increasingly popular with both consumers and researchers for monitoring activity and for promoting positive behavior change. However, there is a lack of research investigating the performance of these devices in free-living contexts, for which findings are likely to vary from studies conducted in well-controlled laboratory settings.ObjectiveThe aim was to compare Fitbit One and Jawbone UP estimates of steps, moderate-to-vigorous physical activity (MVPA), and sedentary behavior w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 36 publications
3
84
0
7
Order By: Relevance
“…The Fitbit substantially overestimates daily step activity and daily minutes spent in moderate, vigorous, and moderate-vigorous physical activity activities compared with the ActiGraph, which is in line with previous research (8,10). However, Gomersall et al (14) reported that the Fitbit One underestimated daily minutes of daily minutes of moderate-vigorous physical activity with 19.2 minIday . On the basis of these findings-when being compared with the ActiGraph, the Fitbit is not suitable to assess intensity levels of physical activity in daily life.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The Fitbit substantially overestimates daily step activity and daily minutes spent in moderate, vigorous, and moderate-vigorous physical activity activities compared with the ActiGraph, which is in line with previous research (8,10). However, Gomersall et al (14) reported that the Fitbit One underestimated daily minutes of daily minutes of moderate-vigorous physical activity with 19.2 minIday . On the basis of these findings-when being compared with the ActiGraph, the Fitbit is not suitable to assess intensity levels of physical activity in daily life.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, the Fitbit underestimated the energy expenditure compared with indirect calorimetry. So far, only three studies examined the validity of the Fitbit One in daily life (10,14,20). High Pearson"s r and intraclass correlations were reported for steps taken per day compared with the ActiGraph (10).…”
mentioning
confidence: 99%
“…Satellite navigation on cell-phones allows precise walking/running track recording, etc. There are numerous (commercial) activity trackers available which are validated by multiple studies [82][83][84][85][86] such as the SenseWear armband ® (BodyMedia Inc., Pittsburgh, PA, USA), Fitbit ® (Fitbit Inc., San Francisco, CA, USA), Garmin activity trackers (Garmin, Olathe, KS, USA), Jawbone (San Francisco, CA, USA), and many more. Although recent research showed that all these monitors did have error ranges in free-living conditions [82][83][84], it is also suggested that these activity trackers can offer an opportunity to stimulate health, fitness, and quality of life [82,87], particularly when used for consumer-based self-monitoring to encourage behavioral changes [85].…”
Section: Pa Monitoring and Stimulation (10/23)mentioning
confidence: 99%
“…There are numerous (commercial) activity trackers available which are validated by multiple studies [82][83][84][85][86] such as the SenseWear armband ® (BodyMedia Inc., Pittsburgh, PA, USA), Fitbit ® (Fitbit Inc., San Francisco, CA, USA), Garmin activity trackers (Garmin, Olathe, KS, USA), Jawbone (San Francisco, CA, USA), and many more. Although recent research showed that all these monitors did have error ranges in free-living conditions [82][83][84], it is also suggested that these activity trackers can offer an opportunity to stimulate health, fitness, and quality of life [82,87], particularly when used for consumer-based self-monitoring to encourage behavioral changes [85]. Various studies have used and validated activity trackers to measure PA in both healthy controls [88,89] and CKD patients [90][91][92] and showed that this objective measure is more accurate than self-reported PA by questionnaires, which often over-or underestimates a patients' PA level [93].…”
Section: Pa Monitoring and Stimulation (10/23)mentioning
confidence: 99%
“…While this research generally shows reasonable acceptance among varied user groups, there remain gaps in understanding the spatial accuracy of each of these devices -particularly those that are available on the consumer market and thus could facilitate population-level research. Therefore, building on prior health informatics research examining the accuracy of other types devices used in research [14,15], we compare the accuracy of two widely-available location-tracking devices which determine location using two different technical approaches (described further below).…”
Section: Introductionmentioning
confidence: 99%